Tingkat Kerawanan dan Arahan Pengendalian Pengurangan Risiko Bencana Banjir di Kecamatan Mandonga, Kota Kendari - Tamburaka, Erny; Hasddin, Hasddin (Universitas Diponegoro, Indonesia, 2021)
The purpose of this study was to analyze the level of vulnerability and direction of flood control in Mandonga District, Kendari City. The study used a quantitative descriptive design and a survey. The population and sample of the research in Mandonga District, the informants were determined by purposive sampling. Data were analyzed spatially (GIS namely ArcView 3.2) and descriptive qualitative. Flood vulnerability in Mandonga District, Kendari City is in â€œhighâ€ vulnerability covering an area of 137.02 ha or 31.55%; â€œMediumâ€ vulnerability covering an area of 79.07 ha or 18.21%; and â€œlowâ€ vulnerability covering an area of 218.14 ha or about 50.24%. The directions for flood control that can be taken are construction and repair/maintenance of infrastructure such as drainage; river normalization; manufacture of injection wells (Atificial Recharge) and infiltration wells; integrated sewer; application of bioretical technology; creation of green open areas (RTH); and afforestation or reforestation.